Polysaccharide dispersions : chemistry and technology in food - Walter, Reginald Henry, 1933- (Food science and technology international series., 1998)
Polysaccharides are the subject of heightened interest today, and this book is a concise and fully up-to-date study of the properties of food polysaccharides, describing their interaction with water, the mass-volume-pressure-relationship, various types of mathematical modeling, and the common phenomenology under different combinations of stimuli. New empirical and theoretical equations, which are not often identified with food technologies, are used to support the findings. Polysaccharide Dispersions: Chemistry and Technology in Food is written in a simple, nontechnical style and should be equally comprehensible to the student, the researcher, the plant manager, and the casual observer with only a modest technical background. Key Features * Contains fundamental principles, practical applications, and new discoveries regarding polysaccharides * Presents material in a simple, easy to understand style * Focuses exclusively on the food industry.